EKSTRAKURIKULER “TARI PESISIR” SEBAGAI STRATEGI PENANAMAN PERCAYA DIRI PESERTA DIDIK MIS HIDAYATUL MUHAJIRIN PALANGKA RAYA - Istiyati Mahmudah; Muhibah Amaliyah; Fitriani Fitriani; Dwi Ayu Lestari (Universitas Negeri Makassar, 2023)
This study aims to find out the strategies for instilling confidence in MIS Hidayatul Muhajirin Palangka Raya students through the extracurricular